2010
DOI: 10.4067/s0716-97602010000300012
|View full text |Cite
|
Sign up to set email alerts
|

Sexual orientation, handedness, sex ratio and fetomaternal tolerance-rejection

Abstract: Fraternal birth order (FBO) appears as a prenatal cause of 15% of homosexual males (gays) through mnemonic maternal anti-male factors. Non-right-handed men seem to be protected from homosexuality. Four hypotheses are proposed: (1) androgenic factors of nonright-handedness neutralize anti-male factors; (2) non-right-handedness and homosexuality are lethal or produce mental impairment; (3) non-right-handed male embryos are insensitive to anti-male factors; (4) mothers of non-right-handed fetuses do not produce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 69 publications
1
3
0
Order By: Relevance
“…Although the aforementioned biomarkers of male sexual orientation have been studied rather extensively in isolation, little research has investigated the relationships among them. A few studies considered both birth order and handedness, finding that the fraternal birth order effect is only related to sexual orientation in righthanded gay men (i.e., not mixed or left-handed men) (45,51,53,54). These results are consistent with the possibility that different male sexual orientation biomarkers delineate distinct biodevelopmental pathways and the existence of subgroups of gay men.…”
supporting
confidence: 63%
“…Although the aforementioned biomarkers of male sexual orientation have been studied rather extensively in isolation, little research has investigated the relationships among them. A few studies considered both birth order and handedness, finding that the fraternal birth order effect is only related to sexual orientation in righthanded gay men (i.e., not mixed or left-handed men) (45,51,53,54). These results are consistent with the possibility that different male sexual orientation biomarkers delineate distinct biodevelopmental pathways and the existence of subgroups of gay men.…”
supporting
confidence: 63%
“…This difference is maintained in samples from blood donors, along with the SES, in the English study (Beardmore and Karimi-Booshehri, 1984) and among samples of medical students (high SES), a random sample of children participating in a longitudinal study (low SES), blood donors and blood receptors in Chile (Valenzuela and Harb, 1977;Valenzuela et al, 1980;Valenzuela, 1988). Alternatively a cytogenetic process named consociated chromosome segregation (the Y chromosome may be associated preferentially to one chromosome 9, where the ABO system is coded, see Valenzuela et al, 1980) and a strong association of ABO, Rh and other genetic systems with the sex ratio at birth , Valenzuela, 2010 can partially explain this association in Chile, but not in England. Thus the interaction of the SGC with gender is additional evidence for the true relationship between genetic factors and SES.…”
Section: The Sgc Interacts With Sexmentioning
confidence: 99%
“…It is interesting to remark how the huge advances in Physics, Biology (evolution, genetics and genomics), Chemistry, Cybernetics, and other scientific disciplines are not full accepted and incorporated into philosophies, ethics and theologies. Now we know there are genes involved in sexual fidelity, polygamy and monogamy and others behavioral traits with ethical or moral transcendence in animal and humans [44][45][46]; the prenatal conditioning of sexual phenotypes such as trans-sexuality and homosexuality has been also established by studies on the influence of sibling birth order in sexual orientation and sexual identity [47][48][49] and in studies of human mutants for "sexual" hormones [50][51][52][53]; we also found a great sex dimorphism, at birth and the following years, in the serotonergic nuclei of the brain stem involved in sexual dimorphic behaviors [54,55]. However, moral-theologians, ethicists, bioethicists and lawyers do not seem to have included these facts into their analyses.…”
Section: Conclusion: Is It the Galileo's Case Again?mentioning
confidence: 99%